2012
DOI: 10.1021/jp3087495
|View full text |Cite
|
Sign up to set email alerts
|

Is Photooxidation Activity of {001} Facets Truly Lower Than That of {101} Facets for Anatase TiO2 Crystals?

Abstract: The effect of particle size and active surfaces on photoreactivity of TiO2 crystals is investigated in this report. The clarification of highly active surfaces is the key to understanding the photoreactivity of anatase TiO2 crystal and also to morphological control of photocatalysts with well-defined crystal facets. The anatase TiO2 single crystals with different percentage of {001} facets in uniform size, as well as anatase TiO2 single crystals with different particles size in same percentage of {001} facets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 50 publications
0
64
0
1
Order By: Relevance
“…In addition to crystal phase, crystal disorder [100], exposing highly reactive facets [101], and point defects [102] also play an important role in TiO 2 photocatalysis and its other applications (self-cleaning, cosmetics, paper, etc.). In the case of anatase, (101) facets (surface energy of 0.44 J/m 2 ) are thermodynamically stable than the much more reactive (001) facet (surface energy of 0.90 J/m 2 ) [103].…”
Section: Page 6 Of 70mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to crystal phase, crystal disorder [100], exposing highly reactive facets [101], and point defects [102] also play an important role in TiO 2 photocatalysis and its other applications (self-cleaning, cosmetics, paper, etc.). In the case of anatase, (101) facets (surface energy of 0.44 J/m 2 ) are thermodynamically stable than the much more reactive (001) facet (surface energy of 0.90 J/m 2 ) [103].…”
Section: Page 6 Of 70mentioning
confidence: 99%
“…In the case of anatase, (101) facets (surface energy of 0.44 J/m 2 ) are thermodynamically stable than the much more reactive (001) facet (surface energy of 0.90 J/m 2 ) [103]. Both, theoretical and experimental studies have found that the minority (001) facets in the equilibrium state (surface energy of 0.90 J/m 2 ) are much more active with respect to (101) facet, due to their higher surface energy [104]. For these reasons, the researchers have devoted much more attention to the synthesis of TiO 2 with exposed (001) facet crystals.…”
Section: Page 6 Of 70mentioning
confidence: 99%
“…The first approach is known as a wet-chemistry route related to hydrothermal reactions. This approach involves the application of fluorinecontaining species (e.g., hydrogen fluoride, ammonium fluoride, titanium(IV) fluoride and tetrafluoroborate ion) as morphology-controlling agents to prevent the formation of more thermodynamically stable octahedral anatase titania particles (OAPs) exposing only {101} facets [22][23][24][25][26][27][28][29][30][31][32][33]. Other compounds including polyvinyl alcohol [34,35] and carbonate ions generated during decomposition of urea have also been used to control the shape [20].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of {001} facets is greater than that of {101} facets if the crystal sizes of anatase TiO 2 are identical. [32] Thus, our hollow single crystals may have improved photochemical activities relative to those of large particles with {001} facets and similars olid nanocrystals with {101} or even {001} facets.…”
Section: Introductionmentioning
confidence: 96%
“…However,i ti ss afe to conclude that the outer and inner surfaces should be {101} facets because they have the lowest surface area. Ar ecent study showed that the dominant factor for the photocatalytic activity of anatase TiO 2 was particle size, [32] which was related to the surface area and active sites. The activity of {001} facets is greater than that of {101} facets if the crystal sizes of anatase TiO 2 are identical.…”
Section: Introductionmentioning
confidence: 99%